Determining the dynamic loading on a semi-wagon when fixing it with a viscous coupling to a ferry deck - Fomin, Oleksij; Lovska, Alyona; Kulbovskyi, Ivan; Holub, Halyna; Kozarchuk, Ihor; Kharuta, Vitalii (Eastern-European Journal of Enterprise Technologies, 2019)
We have modeled the dynamic loading of a semi-wagon body when it is fixed by a viscous coupling relative to the deck of a railroad ferry. The relevance of this research relates to the fact that the movement of wagons by sea on railroad ferries is accompanied by the effect of significant magnitudes of loads on the load-bearing structures of their bodies. The numerical values of these loads are significantly higher than those that act on a wagon under operation along a railroad. In addition, the current scheme does not ensure the reliability of fastening the body and thus causes damage to its structural elements. This necessitates conducting unplanned repairs of wagons that are transported on railroad ferries. It is therefore proposed to improve the scheme of fixing a wagon relative to the deck of a railroad ferry. In order to mitigate the effect of loads exerted by chain couplers on a wagon body, it is suggested that they should be connected by a flexible link, rather than rigid, by installing a specialized device ‒ a damper between a body and a deck. To simulate the dynamic loading of a wagon body taking into consideration the proposed technical solutions, a mathematical model has been constructed and the magnitudes of accelerations acting on the body have been determined. The model accounts for the movement of a railroad ferry with wagons under side rocking motion as one of the main types of vessel fluctuations. It was established that it becomes possible, by taking into consideration the proposed scheme of fixing a wagon body relative to the deck, to reduce the magnitude of its dynamic loading by 30 %. We have also determined the dynamic loading on a wagon body by computer simulation in the programming environment CosmosWorks. Numerical values and the fields of deployment of semi-wagon body’s accelerations have been determined. The constructed models were verified based on an F-criterion. The present research will contribute to maintaining the bearing structures of wagons’ bodies when they are transported on railroad ferries, as well as improving the efficiency of their operation along international transport corridors